Meningkatkan Aktivitas, Keterampilan Berpikir Kritis, Dan Hasil Belajar Muatan PPKn Kelas IV A Menggunakan Model Pesat Di SDN Manarap Lama 1 - Nabilla Azahra; Fathul Jannah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
The research aims to address the issue of low activity, critical thinking skills, and learning outcomes in students. To overcome this problem, the PESAT model is introduced in the learning process. The study focuses on teacher activities, student activities, critical thinking skills, and student learning outcomes. The research employs Classroom Action Research (PTK) and is conducted at three meetings. The subjects are students from Class IV A of SDN Manarap Lama 1 in the second semester of the 2022/2023 academic year, with a total of 22 students. The research uses a combination of qualitative and quantitative approaches. Data analysis involves descriptive techniques, with results presented in tables, graphs, and percentages. The findings indicate that educators' activities receive a score of 32 based on the "Very Good" criterion. Student activity increases by 91% using the "Almost All Students Are Very Active" criterion. Critical thinking skills improve by 100% using the "All Students Very High" criterion. Learning outcomes also increase by 100% using the "Very Good" criterion. In conclusion, the use of the PESAT model leads to increased activity, critical thinking skills, and learning outcomes. These results can serve as a reference for future research and the implementation of the PESAT model in educational settings..